Model of Land Cover Change Caused by Toll Road Access Using Cellular Automata in Sumatra Island - Zenia F Saraswati; Acep Purqon; IB Ilham Malik; Dion Awfa; Fajriharish Nur Awan; M Risky; Melisa Vira Permata; Maulidya Paramitha; Iqbal Wira Menanza; Nasrul Putra (Universitas Bandar Lampung (UBL), 2022)
The use of land is a part of the fulfillment of human needs. The establishment of a large-scale infrastructure project often triggers an increase in land cover around its infrastructure project. Most of the increase in built up land tends to occur in areas that are traversed by or located near main accessibility routes such as toll roads. Although the construction of toll roads can improve accessibility between regions, land is a limited resource. So that it becomes the basis for researchers to identify the changes in land use in regencies and cities on the island of Sumatra that are crossed by toll roads that have been operating. The goal of land use change analysis is to give a description or explanation, predict, look at the effects, and make a decision (prescription). This research was conducted by identifying the changes in the existing land cover and predicting the land cover using cellular automata. Cellular automata have proven to be a method that is suitable for predicting the dynamics of land use through spatial simulation. The results show that there was an increase in the amount of land built from early 2017 to 2030. The covered land is developed around the toll gate after it is actively operated. In all provinces studied, deviation discrepancies were found in the conservation and cultivation areas. Deviations that occur in conservation areas need to be considered as there should be no land built in these areas, which means that there are cultivation activities in the conservation areas.